Degradation of chlorobenzene and 2-chlorotoluene by immobilized bacteria strains Comamonas testosterone kt5 and Bacillus subtilis dkt - Duc, Ha Danh; Oanh, Nguyen Thi (Academia Journal of Biology, 2019)
Chlorobenzenes and chlorotoluenes have been used to produce a number of industrial products. They are toxic and widely detected in environments due to human contributory negligence. In this article, the mixed culture of a toluenes-degrading bacterial strain, Comamonas testosterone KT5 (a Gram-positive, catalase-positive bacterium) and a chlorobenzenes-degrading bacterial strain, Bacillus subtilis DKT (a Gram-negative soil bacterium) effectively degraded both chemical compounds co-contaminating in liquid media. In addition, the degradations of mixed compounds by biofilm, bacteria immobilized in polyurethane foam (PUF) and alginate were determined. The results showed that the degradation of both compounds by cells in alginate was significantly higher than that by suspended cells. Moreover, cells immobilized in these materials showed lower adverse effects than those of non-immobilized cells for long-term storage. For examples, the degradation rates for chlorobenzine and 2-chlorotoluene by resting cells reduced by 39.5% and 37.3% after storage for 4 months at 4°C, while the degradation rates by immobilized cells decreased by from 16.3% to 19.8% respectively.